Insights into the electronic and redox behavior of surface-phosphated ceria catalysts in correlation with their propane oxydehydrogenation performance. Issue 10 (4th March 2021) - Popescu, Ionel; Marcu, Ioan-Cezar
Abstract : The addition of P to CeO2 gives surface-phosphated materials showing mainly an electronic conductivity, a reduced lattice oxygen mobility and less active but more selective catalytic sites in propane oxydehydrogenation. Abstract : In situ electrical conductivity measurements (ECMs) have been employed to gain insights into the redox and electronic behavior of ceria and surface-phosphated ceria catalysts with phosphorus contents lower than 2.2 at%. Temperature-programmed reduction under hydrogen (H2 -TPR) was used to analyze the reducibility of the catalysts. Their propane oxydehydrogenation performance both in terms of activity and selectivity has been explained. It has been unambiguously shown that all the catalysts function via a heterogeneous redox mechanism involving only surface and subsurface lattice oxygen species whose availability and reactivity decrease with increasing phosphorus content with consequences on the catalytic performance.